O26-4 Inverse associations between occupational organic dust exposure and incidence of chronic obstructive pulmonary disease (copd) – healthy worker survivor bias?. (1st September 2016) - Vested, Anne; Basinas, Ioannis; Heederik, Dick; Jacobsen, Gitte; Kolstad, Henrik; Kromhout, Hans; Omland, Øyvind; Sigsgaard, Torben; Toft, Gunnar; Thulstrup, Ane Marie; Vestergaard, Jesper; Elholm, Grethe; et al.
Abstract : Background: Organic dust exposure common in the farming and wood industry is a suggested risk factor for COPD. Aims: To investigate exposure-response relations between different exposure metrics for organic dust and the incidence of COPD in the farming and wood industry. Methods: We identified 35, 957 blue-collar workers and followed them since their first employment in farming or wood industry 1997–2007. Information on exposure was obtained from two industry-based exposure matrices with time-dependent quantitative exposure estimates for organic dust in farming and wood industry. Incident COPD cases as defined by ICD-codes 1997–2013 were identified in the Danish national patient register. We analysed data with discrete-time hazard logistic regression with person-years as the unit of analysis and adjusted for age, sex, calendar year, and labour market attachment. Results: We observed an inverse association between levels of organic dust and COPD (P trend < 0.0001). The adjusted RRs (95% CIs) for cumulative exposure for the 2nd, 3rd, and 4th exposure quartiles compared with the 1st were; 1.01 (0.82; 1.26), 0.66 (0.51; 0.84), and 0.70 (0.53; 0.91). Comparable results were seen for average exposure and exposure duration. Analyses on a subset of the population with individual smoking information showed a slightly declining prevalence of smokers with increasing organic dust exposure, but adjusting for smoking did not affect the observed associations. Conclusions: We found an inverse association between organic dust exposure and COPD. In this inception cohort our results should be less affected by a healthy hire effect or left truncation bias, although this can still not be ruled out completely. We find it unlikely that the declining risk of COPD reflects a gainful effect of organic dust exposure, but rather healthy worker survivor bias related to exposure level, smoking, or other underlying individual factors associated with exposure level even if our sub-analyses were unable to detect a confounding effect of smoking.